2017
DOI: 10.1200/jco.2017.72.6463
|View full text |Cite
|
Sign up to set email alerts
|

CONKO-005: Adjuvant Chemotherapy With Gemcitabine Plus Erlotinib Versus Gemcitabine Alone in Patients After R0 Resection of Pancreatic Cancer: A Multicenter Randomized Phase III Trial

Abstract: Purpose Gemcitabine is standard of care in the adjuvant treatment of resectable pancreatic ductal adenocarcinoma (PDAC). The epidermal growth factor receptor tyrosine kinase inhibitor erlotinib in combination with gemcitabine has shown efficacy in the treatment of advanced PDAC and was considered to improve survival in patients with primarily resectable PDAC after R0 resection. Patients and Methods In an open-label, multicenter trial, patients were randomly assigned to one of two study arms: gemcitabine 1,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
171
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 246 publications
(180 citation statements)
references
References 25 publications
4
171
0
5
Order By: Relevance
“…With 3 years of follow-up, the emerging durability data on OS and DFS in this trial are encouraging when viewed in the context of current literature reporting large-scale trials with gemcitabine as monotherapy, which range from 10.7 to 13 months for DFS, and 17.1 to 26.5 months for median survival. 4,5,[15][16][17][18][19] Based on time from surgery, in this study median DFS was 16.1 months and median OS was 33.3 months for the total study population, which compare favourably with published data for gemcitabine monotherapy, and indeed even with gemcitabine and capecitabine combination therapy (GemCap). Modification of the vaccination schedule, whilst appearing to eliminate the risk of allergic reactions, did not appear to compromise this encouraging efficacy.…”
Section: Discussionsupporting
confidence: 82%
“…With 3 years of follow-up, the emerging durability data on OS and DFS in this trial are encouraging when viewed in the context of current literature reporting large-scale trials with gemcitabine as monotherapy, which range from 10.7 to 13 months for DFS, and 17.1 to 26.5 months for median survival. 4,5,[15][16][17][18][19] Based on time from surgery, in this study median DFS was 16.1 months and median OS was 33.3 months for the total study population, which compare favourably with published data for gemcitabine monotherapy, and indeed even with gemcitabine and capecitabine combination therapy (GemCap). Modification of the vaccination schedule, whilst appearing to eliminate the risk of allergic reactions, did not appear to compromise this encouraging efficacy.…”
Section: Discussionsupporting
confidence: 82%
“…Targeting this key pro-tumourigenic molecular pathway has been explored in PDAC with the combination of standard therapy gemcitabine and small molecule EGFR inhibitor erlotinib revealing a modest but significant improvement in patient survival in advanced disease [175][176][177]. However, significance was lost when this combination was trialled in all-comers in the adjuvant setting [178]. Further analyses revealed that therapeutic benefit of combined gemcitabine/EGFR inhibition associated with KRAS wild-type tumour status [179,180] or development of skin rash in patients, which represents another measure of EGFR inhibitor activity [181].…”
Section: Targeting Src Kinase In Pancreatic Cancermentioning
confidence: 99%
“…Surgical resection with adjuvant chemotherapy is the current standard of care. Recent trials have reported improved median overall survival to 24·5–28 months with adjuvant treatment. However, these trials did not report how many eligible patients were fit enough to be randomized to receive adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%